Kualitas pelayanan publik bagi costumer parfum - Suryati, Suryati - (Maliki Interdisciplinary Journal, 2023)
The quality of public services in one of the main key factors in building relationships between government and society. In the context of the parfume industry, high quality public services are important because costumers have high expectations for the products and services they receive. This research aims to explore aspects of public service quality that influence costumer satisfaction in the parfume industry. The research method used is field research by collecting data trought interviews and surveys with perfume costumers. The research results show that there are several aspects of public service quality that play an important role in influencing costumer satisfaction. Some of them include product quality, price, consumer behavior, and brand image. Good quality public service and help create long-term relationships between costumers and perfume brands, which in turn can increase busines success.